Analysis on Financial Performance Influence Toward Market Performance with ERM (Enterprise Risk Management) Implementation Category as Moderator Variable - Hemmy Fauzan; Deni Pandu Nugraha (Journal of International Conference Proceedings (JICP), 2018)
This research examines financial performance influence toward market performance with ERM Implementation as moderator variable. This research hypothesis that financial performance has positif significant influences toward market performance, the influence of financial performance toward market performance company with ERM is higher than company nonERM and market performance company with ERM is higher than company nonERM. The results of the study do not support the hyphotesis. Examined result shows that statiscally market performance is not influenced by financial performance achievement, although not significant financial performance influences over company with ERM has show higher positif relation than company nonERM toward market performance. Keywords: ERM, Performance, Financial, Market.